2014
DOI: 10.1186/1472-6882-14-323
|View full text |Cite
|
Sign up to set email alerts
|

Variations in energy metabolism along the pericardium meridian and its relationship with visceral function adjustments during electroacupuncture

Abstract: BackgroundElectroacupuncture (EA) is a traditional Chinese medicine treatment guided by meridian theory. As it gradually gains more worldwide acceptance, a clarification of its mechanisms is extremely urgent. We observed variations in transcutaneous oxygen pressure/carbon dioxide pressure (tcpO2/tcpCO2) and microcirculation blood perfusion units (BPU) along the pericardium meridian, and cardiac function during EA at Neiguan (PC6) to explore variations in energy metabolism and its relationship with visceral fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…In addition, the values of tcp CO 2 at acupoints were lower than those at their bilateral corresponding control points. In comparison, in the normal state, electroacupuncture could decrease tcp O 2 along the meridian significantly and increase tcp CO 2 [29]. These results are also somewhat different from other reports; however, there is general agreement that acupuncture can increase the energy metabolism at acupoints, i.e., metabolism-related oxygen and oxygen metabolites will show corresponding changes, representing the oxygen specificity of acupoints.…”
Section: Studies On Carbon Dioxide and Acupointscontrasting
confidence: 51%
“…In addition, the values of tcp CO 2 at acupoints were lower than those at their bilateral corresponding control points. In comparison, in the normal state, electroacupuncture could decrease tcp O 2 along the meridian significantly and increase tcp CO 2 [29]. These results are also somewhat different from other reports; however, there is general agreement that acupuncture can increase the energy metabolism at acupoints, i.e., metabolism-related oxygen and oxygen metabolites will show corresponding changes, representing the oxygen specificity of acupoints.…”
Section: Studies On Carbon Dioxide and Acupointscontrasting
confidence: 51%
“…As a connection, adjustment, and response system, it is more likely that the essence of meridians involves very complex physical structures, including some currently unknown structures [ 16 ]. Some studies found that meridians may be channels of multiple structures that transform and transmit materials, heat, energy, and messages [ 16 , 36 ]. Moreover, the intensity of heat transmission along the meridian direction is more significant than that along the nonmeridian direction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Traditional Chinese Medicine (TCM) has been gaining more and more attention as the traditional therapy of complementary and alternative medicine (CAM) in the world due to its simplicity, convenience, efficiency, and cheapness [1][2][3]. ere is a growing amount of studies on specificities of meridian acupoints through biophysics [4][5][6], electrophysiology [7][8][9], infrared imaging [3,10], and so forth.…”
Section: Introductionmentioning
confidence: 99%